THE PROBLEMS OF MODELING AN EXPERT AND ANALYTICAL TASKS WITH TAKING INTO ACCOUNT WELL-SPECTRAL DATA AND FACTORS - Bandorina, L. M.; Savchuk, L. M.; Klymkovych, T. O. (Science and Transport Progress, 2009)
In the paper there are considered the theoretical aspects of realization for well-grounded transition from classic stochastic models and expert judgments to fuzzy-set descriptions at modeling of expert analytic systems.